Privatisation, political risk and stock market development in emerging economies - Enrico C. Perotti; Pieter van Oijen (Fondazione Eni Enrico Mattei (FEEM), 1999)
This paper investigates whether privatisation in emerging economies has a significant indirect effect on local stock market development through the resolution of political risk. We argue that a sustained privatisation programme represents a major political test which gradually resolves uncertainty over political commitment to a market-oriented policy as well as to regulatory and private property rights. We present evidence suggesting that progress in privatisation is correlated with improvements in perceived political risk. These gains tend to be gradual over the privatisation period and are significantly larger in privatising countries than in nonprivatising countries, suggesting that the resolution of such risk is endogenous to the privatisation process. Our analysis shows further that changes in political risk in general tend to have a strong effect on local stock market development and excess returns in emerging economies, suggesting that political risk is a priced factor. We conclude that the resolution of political risk resulting from successful privatisation has been an important source for the rapid growth of stock markets in emerging economies.
Keywords: G15; G18; G38; F30; 330; Privatisation; Political risk; Stock market development; Privatisierung; Aufstrebende Märkte; Aktienmarkt; Kapitalmobilität; Länderrisiko; Welt